RELEVANSI PRODUKSI AIR MINUM KH-Q DENGAN WASIAT KH. MUHAMMAD ARWANI BERDASARKAN AYAT WA LĀ TAṠTARŪ BI ᾹYĀTĪ ṠAMANĀN QALĪLĀN - Azka Noor (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
This paper contains the search for the meaning of buying and selling verses contained in Qs. al-Baqarah verse 41 and the context of its use in the Qur’an according to the mufassir's perspective, as well as the perspective of KH. Muhammad Arwani, in an effort to find answers to the assumptions of some people regarding the production of Kh-Q drinking water by PT. Buya Barokah is under the auspices of the Arwaniyyah Foundation Business Entity which is temporarily viewed by some as an act of trading verses. The author uses the maudhui thematic method as a whole verse and the interview method with zurriyyah (Family) and related people as well as observations to collect data and analyze it in order to find answers that can be accounted for. in this case the author uses analytica l descriptive method. The results of the study show that there is no element of searching for something worldly from selling Kh-Q and not like what is contained in Qs. al-Baqarah verse 41, so the author does not find any relevance between Kh-Q products and KH. Muhammad Arwani’s testament regarding the prohibition of trading verses based on Qs. al-Baqarah verse 41.